Analisis Faktor-Faktor Yang Mempengaruhi Manajemen Laba Dan Pengaruhnya Terhadap Biaya Modal Ekuitas Pada Sektor Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Puspitosari, Indriyana (EBBANK, 2013)
This study aims to analyze the effect of leverage, managerial ownership, institutional ownership and firm size on earningsmanagement and its implications for cost of equity capital. The population in this study was a banking company listed on the Indonesia Stock Exchange. Samples used in this study were as many as 13 companies since 2007-2010. Independent variables used in this study were leverage, managerial ownership, institutional ownership and firm size. While the dependent variable was cost of equity capital. Earnings management as an intervening variable.Based on the results of multiple linear regression analysis, the study concluded that leverage, managerial ownership, institutional ownership and firm size have no significant effect on earnings management. In addition, the research found that earnings management have no significant effect on cost of equity capital.